2021
DOI: 10.15575/psy.v8i1.6271
|View full text |Cite
|
Sign up to set email alerts
|

Tipe-Tipe Kualitas Perkawinan Orang Yogyakarta

Abstract: This study aims to explore the types of marital quality. A survey was distributed to 316 participants with the characteristics of having been married for at least five years and identified themselves as people of Yogyakarta, which were obtained purposively. The instrument used marital quality scale which was analyzed quantitatively using cluster analysis. Grouping using cluster analysis was based on indicators of marital quality, namely connectivity, passion, complementarity, mutual respect, mutual acceptance,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Characteristics used to determine the clusters were derived from previous research which found three major clusters of marital quality (Nurhayati, 2017;Nurhayati, 2021;Setiawati & Nurhayati, 2020). Analyses with 4-and 5cluster models were also conducted to assess the best model with the best conceptual clarity for the cluster analysis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Characteristics used to determine the clusters were derived from previous research which found three major clusters of marital quality (Nurhayati, 2017;Nurhayati, 2021;Setiawati & Nurhayati, 2020). Analyses with 4-and 5cluster models were also conducted to assess the best model with the best conceptual clarity for the cluster analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Some problems are deeply imprinted but left unsolved. Therefore, despite looking harmonious, couples do not necessarily feel happy (Nurhayati, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…15 The basis for decision making according to G.R Terry is based on intuition, experience, facts, authority, rationality. 16…”
Section: Digital Technology Convergencementioning
confidence: 99%